How to twist a dragon's tale - Cowell, Cressida (New York : Little, Brown and Co., 2010)
Someone has stolen the fire stone, so eggs of exterminator dragons are hatching. Hiccup must return the fire stone to the volcano to save the Tribes from being wiped out.
Includes excerpt from the next book, A hero's guide to deadly dragons.
NC 1070
Accelerated Reader AR
Keywords: Haddock, Hiccup Horrendous, III (Fictitious character) -- Juvenile fiction; Vikings -- Juvenile fiction; Dragons -- Juvenile fiction; Fantasy fiction